(untitled) (Terr@ Plural, 2019)
The Appalachian Geopark (AG) Project is situated in three southern West Virginia (USA) counties: Fayette, Greenbrier and Raleigh. They include the components of rivers, caves and coal; as well as transportation modes, including rail, and country roads. Perhaps most importantly, AG includes the heritage of the people living in the Appalachians. West Virginia University is the entity responsible for developing AG, and will hand over the leadership to local grass roots entities. With this project, the Geopark concept can be linked to a revitalization effort in southern WV, offer new opportunities to develop the communities, and forge a sustainable future. A preliminary geosite inventory exposes nearly 100 geosites. The objective of this paper is present some of the geosites, and discuss future desired conditions. There are no Geoparks in the United States, and Appalachian Geopark is proposed to fill this gap.